(untitled) (Clinics, 2008)
BACKGROUND: Calculating the maximum heart rate for age is one method to characterize the maximum effort of an individual. Although this method is commonly used, little is known about heart rate dynamics in optimized beta-blocked heart failure patients. AIM: The aim of this study was to evaluate heart rate dynamics (basal, peak and % heart rate increase) in optimized beta-blocked heart failure patients compared to sedentary, normal individuals (controls) during a treadmill cardiopulmonary exercise test. METHODS: Twenty-five heart failure patients (49±11 years, 76% male), with an average LVEF of 30±7%, and fourteen controls were included in the study. Patients with atrial fibrillation, a pacemaker or noncardiovascular functional limitations or whose drug therapy was not optimized were excluded. Optimization was considered to be 50 mg/day or more of carvedilol, with a basal heart rate between 50 to 60 bpm that was maintained for 3 months. RESULTS: Basal heart rate was lower in heart failure patients (57±3 bpm) compared to controls (89±14 bpm; p